Anthropomorphic Stimuli In Brand Design: The Effect Of Human Face Schema - Harun, Azahar; Abd Razak, Mohamed Razeef; Abd Rahim, Russlan; Mohd Radzuan, Lili Eliana (2016)

(untitled)
Numerous studies claim that creative designers and advertisers often use anthropomorphism as a marketing tool for evoking emotion, facilitating interaction and influencing consumer’s buying decision. Brand names such as KFC, Michelin and M&M earn recognition and popularity due to human characteristic embedded in its logo design. In spite of this, it is unclear what kind of anthropomorphic stimuli that can effectively engage consumers and establish relationship. Hence, we hypothesize that viewers would be more responsive towards symbols that imitates human characteristic. To test this, a visual preference survey was conducted. Based on a scale of 1 Not Familiar to 5 Extremely Familiar, one hundred and nineteen (n=119) participants rated fifteen (15) types of graphic symbol (made of circle, square, triangle, line and dots) which have been embedded with anthropomorphic stimuli. Findings of the study identify several graphic symbols with familiar anthropomorphic stimuli have the ability to influence judgment on visual appeal and acceptance